Factors associated with successful treatment outcomes among tuberculosis patients in a district municipality of Vhembe, Limpopo - Busisiwe Mkhavele; Slindile Zondi; Lindiwe Cele; Mabina Mogale; Margeret Mbelle (South African Family Practice)
Background: Treatment success rate is a critical indicator for monitoring the progress of tuberculosis (TB) treatment programmes at both the patient and population levels. It informs decisions about resource allocation and the effectiveness of TB control strategies. This study aimed to determine the level of TB cure rates and the factors associated with treatment success among TB patients receiving TB care in the Collins Chabane municipality, Limpopo province, South Africa.